EVALUASI KINERJA PEGAWAI KANTOR KEMENTERIAN AGAMA KABUPATEN MAGELANG - Widi Astuti; Meidi Syaflan (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2023)
This writing uses a qualitative method. The subjects in this study were informants who provided information in this study as many as 3 people consisting of 1 Head of the Human Resources Section, 2 administrative employees of the Ministry of Religion. Magelang Regency. Interactive model data analysis as proposed by Miles and Huberman (1992) which includes four components, namely data collection, data reduction, data presentation, conclusion drawing or verification. The results of this study indicate that the factors causing the increase in the performance of the employees of the Ministry of Religion of Magelang Regency are still low in terms of (a) Attitude, the cause is that there are still some employees who are less disciplined at work, lack of guidance. (b) Ability, the reason is that the ability of ASN is not entirely based on qualifications, competence and performance, and the evaluation of personnel services is not yet optimal. (c) achievement (Accomplishment), the reason is that there are still employees who do not match HR competencies, lack of facilities and infrastructure. Then efforts were made to improve the performance of the employees of the Office of the Ministry of Religion of Magelang Regency in terms of: (a) Morality / Personality (Attitude) aspects with efforts to provide exemplary discipline and guidance by the leadership to employees, then given spiritual showers and ESQ (Emotional Spiritual Quotient) training. (b) Ability or (Ability) with efforts to organize employee management training, socialize new laws and regulations, and send employees to attend courses and organize discussions, dialogues, workshops and seminars. (c) Achievement by improving employee performance and then providing rewards and punishments as well as improving infrastructure.